"Listen Well": Sounds and Silences in Nahua Narratives of the Conquest in Book 12 of the Florentine Codex. - Sousa, Lisa (Hispanic American Historical Review, 2026)
Book 12 of the Florentine Codex provides the most comprehensive Indigenous account of the Spanish conquest of Mexico (1519–21). This article analyzes the Nahuatl-language alphabetic texts and images in book 12 to shed light on Nahua aural memory of the encounter between the Mexica and Spaniards, the outbreak of war, and the consequences of conquest. The work shows that Nahua authors and artists described and represented sonic experiences as a rhetorical strategy to highlight shifts of power, represent the chaos of war, and convey the psychological toll of the invasion for the people of Tenochtitlan and Tlatelolco. Nahua descriptions of sounds reveal cultural differences and mutual misunderstandings between Nahuas and Spaniards during the encounter and conquest. Memories of sounds, descriptions of how people endured them physically, and the emotions that they inspired also reveal embodied experiences of the war.